A Proposal for an Improved Distributed MAC Protocol for Vehicular Networks - Aslam, Aqsa
Vehicular Ad-hoc Networks (VANETs) have a significant potential to enable new applications in the vehicular domain, some of which addressing traffic safety. In these networks, the Medium Access Control (MAC) plays an important role in providing an efficient communication channel. Currently, there are two protocols for ITS, proposed in the USA (IEEE WAVE) and in Europe (ETSI ITS-G5). Both cases use the PHY and MAC of IEEE 802.11p, the latter being fully distributed and based on CSMA/CA, thus still prone to collisions. This has led to recent proposals for TDMA-based overlay protocols to prevent collisions but leading to complex synchronization and scalability limitations. In this paper we propose enhancing IEEE 802.11p with an overlay protocol based on Reconfigurable and Adaptive TDMA. We specifically target multiple concurrent applications such as multiple platoons. Our proposal separates between the application level, with its own TDMA round and slots allocated to engaged nodes, e.g., a platoon, and the global level that manages multiple TDMA rounds in a mutually agnostic manner, thus, dynamic and scalable. We believe this is the first applications-oriented MAC protocol proposed for VANETS and we discuss its deployment and potential advantages in two typical uses cases, namely platooning and smart intersections.